Evaluation of The Achievement Development Program for The Student-Level Pencaksilat Sport Branch in Lebak Regency - Dede Imanudin; Rony Mohamad Rizal; Aep Rohendi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to evaluate the pencak silat achievement guidance program for students in Lebak Regency using the CIPP (Context, Input, Process, Product) evaluation model. The subjects of this study consisted of 27 respondents including 24 athletes and 3 coaches from several silat schools who actively participated in coaching and championships at the student level. The method used was evaluative with a descriptive quantitative approach, data collection techniques were carried out through questionnaire distribution. The evaluation results showed that: (1) in the Context component, the average percentage of achievement was 88.24% (Very Good category); (2) the Input component achieved 81.40% (Very Good category), with low notes on the facilities and infrastructure indicators; (3) The Process component achieved 83.92% (Very Good category), but the parental participation indicator only reached 71.67% (Sufficient category); and (4) the Product component achieved 85.42% (Very Good category), with improvements in technique, mentality, and athlete achievement. In general, the evaluation results show that the coaching program has been running very well but still requires strengthening in the provision of training facilities and parental involvement. The results of this study are expected to be a reference for stakeholders in developing more effective and sustainable coaching programs.